Effect of glutathione supplementation during sperm preparation and in vitro fertilization on ovine embryo development - RANGASAMY, S; KULASEKAR, K; BALASUBRAMANIAN, S; RAJ, G DHINAKAR (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to investigate the effect of glutathione (GSH) supplementation duringsperm preparation media (SPM) and in vitro fertilization (IVF) media on ovine embryo development. Sixindependent trials with a total of273 oocytes were carried out with GSH supplementation at 0.3 mg/ ml duringSPM and IVF, 263 oocytes without supplementation formed the control. The mean cleavage rates were 48.46 ±0. l 5 and 46.68 ± 0.12 per cent (P
Keywords: Ovine; Glutathione; In vitro fertilization; Embryo